Impact of body-mass index on treatment and outcome in locally advanced rectal cancer: a secondary, post-hoc analysis of the CAO/ARO/AIO-04 randomized phase III trial - Diefenhardt, Markus; Ludmir, Ethan B.; Hofheinz, Ralf-Dieter; Ghadimi, Michael; Minsky, Bruce D.; Fleischmann, Maximilian; Fokas, Emmanouil; Rödel, Claus (Radiotherapy and oncology, 2021)
Background - A better understanding of the impact of body-mass index (BMI) on the course of multimodal therapy and oncologic outcome in locally advanced rectal cancer could provide new insights for optimization of treatment and supportive strategies. - Patients and methods - Correlations of BMI with pretreatment clinical, surgical, and pathological characteristics, toxicity and treatment adherence using the Pearson’s Chi-squared test or logistic regression were analyzed in the CAO/ARO/AIO-04 III trial cohort (n = 1236). One-way ANOVA or Welch test were used to analyze correlations of baseline blood-parameters and BMI. The prognostic role of BMI was examined with log-rank test and multivariate cox regression. - Results - Obese had a better ECOG performance status (P = 0.027) but were less likely to undergo sphincter preserving surgery (P = 0.01). Post-surgical complications did not differ significantly between BMI classes, whereas underweight was associated with increased neutrophil (P = 0.025) and platelet counts (P < 0.001), poorer TME quality (P = 0.007) and increased incidence of acute organ toxicity (P < 0.001). After a median follow-up of 50 months, underweight [HR 1.896, P = 0.014] and overweight [HR 1.392, P = 0.042] were associated with worse DFS. Obese patients had an increased risk of death [HR 1.653, P = 0.032]. Normalweight men showed superior OS compared to underweight [HR 4.070, P = 0.002], overweight [HR 2.077, P = 0.010], severe overweight [HR 1.886, P = 0.026] and obese [HR 2.046, P = 0.015] men. Adding oxaliplatin to standard CRT significantly improved DFS in obese patients (P = 0.034). - Conclusion - In our study, underweight and overweight correlated with inferior DFS, underweight experienced more organ toxicity and obesity was associated with an increased risk of abdominoperineal resection and poorer overall survival.